Medical mirroring: granulomatosis with polyangiitis (formerly Wegener's) mimicking immunoglobulin‐G4 related disease. (31st July 2015) - Kaushik, Prashant; Stone, John H.; Anderson, James T.; Dugar, Shaifali; Mathew, Roy; Nikolic, Boris; Patel, Raina
Abstract: Granulomatosis with polyangiitis (GPA; formerly Wegener's) can present with clinical and histopathological features similar to those of immunoglobulin‐G4 related disease (IgG4‐RD), a recently described fibro‐inflammatory condition. The ability of these two distinct entities to mimic each other closely creates significant pitfalls in diagnosis. We present a unique case in which GPA presented as a peri‐aortic fibrotic mass in the retroperitoneum. The patient's other clinical features also overlapped with classic IgG4‐RD disease manifestations, but the histopathology in two organs and the serological data confirmed the diagnosis of GPA. Rigorous histopathological review remains the gold standard for the diagnosis of GPA and the distinction of this entity from IgG4‐RD and other mimickers.